The Leuven Embedded Figures Test (L-EFT): measuring perception, intelligence or executive function? - Hanne Huygelier; Ruth Van der Hallen; Johan Wagemans; Lee de-Wit; Rebecca Chamberlain (PeerJ, 2018)
Performance on the Embedded Figures Test (EFT) has been interpreted as a reflection of local/global perceptual style, weak central coherence and/or field independence, as well as a measure of intelligence and executive function. The variable ways in which EFT findings have been interpreted demonstrate that the construct validity of this measure is unclear. In order to address this lack of clarity, we investigated to what extent performance on a new Embedded Figures Test (L-EFT) correlated with measures of intelligence, executive functions and estimates of local/global perceptual styles. In addition, we compared L-EFT performance to the original group EFT to directly contrast both tasks. Taken together, our results indicate that performance on the L-EFT does not correlate strongly with estimates of local/global perceptual style, intelligence or executive functions. Additionally, the results show that performance on the L-EFT is similarly associated with memory span and fluid intelligence as the group EFT. These results suggest that the L-EFT does not reflect a general perceptual or cognitive style/ability. These results further emphasize that empirical data on the construct validity of a task do not always align with the face validity of a task.